Combined Internal and External Fixation for Charcot Neuroarthropathy: A Learning Curve - Muhammed H. Iqbal MD; Sultan N. Qasim FRCS (Tr&Orth); Simon Chambers FRCS (Foot & Ankle Orthopaedics, 2020)
Category: Diabetes; Trauma Introduction/Purpose: Management of complex foot and ankle deformities secondary to charcot neuroathropathy represents a significant challenge. This is a consequence of medical co-morbidities, vascular disease, peripheral neuropathy, and immune compromise with the surgical challenges of progressive bony defomity and bone resorption. To combat these challenges ‘superconstructs’ have been developed to improve fixation. These aim for fusion beyond the zone of injury with adequate deformity correction all whilst maintaining viability of the soft tissue envelope and mechanical function. This can be achieved with internal fixation using indication specific plates and beaming techniques, external fixation with a circular frame or a combination of the two. The aim of this study was to evaluate of a tertiary referral hospital in the operative management of charcot neuroarthopathy. Methods: This is a retrospective two surgeon case series with all cases jointly operated upon. Cases were identified from a locally held diabetic patient registry as those undergoing charcot foot and ankle reconstruction from 2017 to 2019. No exclusion criteria were outlined. Patient demographics and co-morbidities were collected, pre-op radiological markers (meary’s angle) measured and repeated at 6 weeks and one year. Pre-op radiographs were classifed accroding to brodsky classification. Patient outcomes were recorded of amputation, mortality, ulcer recurrence, reported pain, stable heel, ability to ambulate, need for revision surgery, need for prolonged antibiotics, fusion and surgical complications. PROMS were requested and still awaited at time of submission. Results: Eleven Cases were identified from ten patients, all were included for analysis. Three patients had internal fixation, two had external fixation and six had combined internal with external fixation. Eight patients were Brodsky 1, two patients were Brodsky 3 and one patient was Brodsky 2. Limb salvage was 100% with nil amputations, mortality 0%, ulcer recurrence 0%, 100% improved pain score, and 100% with a stable heel. Meary’s angle improved by a mean of 14o from -16o to -2o at 1 year. Fusion rate determined clinically and radiologically with X-ray was 100% with mean of 129 days and range of (360 - 52). Mean follow-up 454 days and range (547-417). Complications of 2 tibial fractures and 1 deep infection with delayed wound healing. Conclusion: The outcomes of using all three methods is positive with 100% limb salvage, 100% fusion rate, 100% ulcer free and maintenace of Meary’s angle at 1 year post op. We believe that combined internal and external fixation, not widely reported in the literature, is a good option in these cases. The complications reported here were in the first three patients undergoing said technique and represent a learning curve.